The Criticism of the Political Model of Humanitys Twitter NU Garis Lucu Against Intolerant Groups and Government - Ghozali, Imam (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This article examines the criticism of the political model of humanity, namely a critique of the political activities carried out by Twitter NU Garis Lucu against intolerant groups and the government that ignores human values. This twitter displays a style of criticizing and introducing new models of political values on social media, namely through witty sentences and humor across religions, ethnicities, and cultures. This model of politics becomes very important at a time when social sedia is filled with negative and provocative comments and narratives that endanger human values. As a result of this narrative, people are trapped in a rigid understanding, cannot accept differences, and easily judge other Muslims to be wrong when the latters opinions do not align with ones own. This attitude in turn leads to an understanding of identity politics based on religion, one that rejects the teaching and symbols of the state, which are in turn considered contrary to the teachings of the sharia. This research is a descriptive and a qualitative analysis of the many reactions against the NU Garis Lucu twitter handle. The first part relates to the Twitter critique of NU Garis Lucu towards intolerant groups[NP1] . The second relates to the critique that the NU Garis Lucu received with regards to its stance against government and politicians. The results of the study show that the humanitarian politics developed by Twitter NU Garis Lucu by criticizing textual Islamic groups that have the potential to divide the harmony of Islamic society and the birth path of radicalism groups that aspire to uphold Islamic law kaffah. His criticism are manifested in dialogical, witty sentences, with an approach to Islamic teachings that are friendly, tolerant, and accept diversity in religious understanding. He also criticized government policies that were detrimental to the community and politicians who often raised identity politics and ignored its substance in fighting for the interests of the community. Artikel ini mengkaji kritik model politik kemanusiaan yaitu suatu kritik terhadap kegiatan politik yang dilakukan oleh Twitter NU Garis Lucu terhadap kelompok-kelompok anti-toleransi dan pemerintah yang mengabaikan nilai-nilai kemanusiaan. Twitter ini menampilkan gaya cara mengkritik dan memperkenalkan nilai-nilai politik model baru di Media Sosial, yaitu melalui kalimat-kalimat jenaka dan humor lintas agama, suku, etnis dan budaya. Politik model seperti ini menjadi sangat penting pada saat media sosial dipenuhi komentar dan narasi-narasi negatif dan provokatif yang membahayakan nilai-nilai kemanusiaan. Akibat dari narasi tersebut, masyarakat terjebak pada pemahaman yang kaku, tidak bisa menerima perbedaan, dan mudah memvonis orang Islam lain salah ketika tidak sesuai dengan pemahamanya, yang merembet pada pemahaman politik identitas yang berdasarkan agama yaitu suatu paham yang menolak ajaran dan simbol-simbol negara yang dianggap bertentangan dengan ajaran syariat. Jenis penelitian ini adalah deskriptif kualitatif untuk untuk mengungkapkan hasil temuan. Pertama berkaitan dengan kritik twitter nu garis lucu kepada kaum intoleran. Kedua berkaitan dengan kritik Twitter NU Garis Lucu terhadap pemerintahan dan politisi. Hasil penelitian memperlihatkan bahwa politik kemanusiaan yang dikembangkan oleh Twitter NU Garis Lucu dengan melakukan kritikan atas kelompok Islam tekstual yang mempunyai potensi memecah belah kerukunan masyarakat Islam dan jalan lahirnya kelompok radikalisme yang bercita-cita menegakan syariat Islam secara kaffah. Kritikan-kritikanya diwujudkan dengan kalimat bersifat dialogis, jenaka, dengan pendekatan ajaran Islam yang ramah, toleran, dan menerima keberagaman dalam pemahaman agama. Ia juga mengkritik terhadap kebijakan pemerintah yang merugikan masyarakat dan para politikus yang sering mengangkat politik identitas dan mengabaikan subtansinya dalam memperjuangkan kepentingan masyarakat.